2022
DOI: 10.1111/1365-2656.13845
|View full text |Cite
|
Sign up to set email alerts
|

Breaking down the components of the competition‐colonization trade‐off: New insights into its role in diverse systems

Abstract: Performance trade‐offs between competition and colonization can be an important mechanism facilitating regional coexistence of competitors. However, empirical evidence for this trade‐off is mixed, raising questions about the extent to which it shapes diverse ecological communities. Here, we outline a framework that can be used to improve empirical tests of the competition‐colonization trade‐off. We argue that tests of the competition‐colonization trade‐off have been diverted into unproductive paths when disper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 93 publications
0
4
0
Order By: Relevance
“…Based on these results, mean seed mass of native species would be expected to increase over time, which was indeed observed (Figure 4b,e). Since seed mass is linked to seedling competition–colonization trade‐offs (Coomes & Grubb, 2003; Ferzoco & McCauley, 2023; Rees, 1996; Turnbull et al., 1999), these patterns likely represent the transition from good colonizers that arrive early to competitively superior species that dominate in later stages. Similarly, taller native species had higher incidence and abundance in late succession as compared to shorter ones (Figures 2 and 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these results, mean seed mass of native species would be expected to increase over time, which was indeed observed (Figure 4b,e). Since seed mass is linked to seedling competition–colonization trade‐offs (Coomes & Grubb, 2003; Ferzoco & McCauley, 2023; Rees, 1996; Turnbull et al., 1999), these patterns likely represent the transition from good colonizers that arrive early to competitively superior species that dominate in later stages. Similarly, taller native species had higher incidence and abundance in late succession as compared to shorter ones (Figures 2 and 3).…”
Section: Discussionmentioning
confidence: 99%
“…For native species, we confirmed that height and seed mass, in particular, significantly explained species composition, consistent with the predictions of deterministic community assembly. In the early stages of succession, small-seeded native species were more likely to be present in the community is linked to seedling competition-colonization trade-offs (Coomes & Grubb, 2003;Ferzoco & McCauley, 2023;Rees, 1996;Turnbull et al, 1999), these patterns likely represent the transition from good colonizers that arrive early to competitively superior species that dominate in later stages. Similarly, taller native species had higher incidence and abundance in late succession as compared to shorter ones (Figures 2 and 3).…”
Section: Species Pool Differencesmentioning
confidence: 99%
“…Our modeling of interference competition as a delay before a motile organism “gives up” is not an obvious fit to sessile plants, although it is, following precedent in classic game theory (Maynard Smith and Price, 1973), a good fit for motile animals (Stanton, Palmer and Young 2002, Rodríguez, Jansson and Andrén 2007, Ferzoco and McCauley 2023). Specifically, temporal investment in interference incurs an opportunity cost to foraging, facilitating coexistence.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous theoretical models highlight the critical role of regeneration processes in shaping forest ecosystems. Competition–colonization models propose that the coexistence of tree species is influenced by their competitive abilities for resources and colonization capacities in different environmental niches [ 24 ]. Species with strong competitive traits may dominate resource-rich areas, while others with efficient colonization mechanisms thrive in less favourable conditions.…”
Section: Introductionmentioning
confidence: 99%